RANCANG BANGUN SISTEM INFORMASI DATA GURU MENGGUNAKAN MODEL RAPID APPLICATION DEVELOPMENT - Kusnanjaya, Ady (Jurnal Pilar Nusa Mandiri, 2013)
Each new school year, teacher to report the activities of teaching and learning process. The report data is processed operational section PEMBIMAS Catholic teachers, teacher data are processed as for the completeness of documents personal data of teachers, teacher certification, retirement, and education history teacher. The processing still using the conventional model is ineffective and inefficient at the time of making the required reports. Rapid Application Development (RAD) is one of the alternatives of the System Development Life Cycle (SDLC) latter is often used in the system design to overcome delays that occur when using a conventional model. Superiority on the model of Rapid Application Development (RAD) is a software development time becomes shorter, accuracy, and relatively low cost compared with the conventional model. In the design of involving users in the design process lead to the user's needs can be met properly and user satisfaction as the system is increasing. There are some things in Rapid Application Development (RAD) model need to pay attention to the things that are important, the team in completing the design, the scope of the system, the user needs, and system performance. Rapid Application Development (RAD) can be one of the references in the development of information systems that meet user needs.